Hubungan Pengetahuan dengan Kepatuhan Pencegahan Komplikasi pada Penderita Hipertensi - Nurul Assyfa; Ahmad Purnama Hoedaya; Ria Inriyana (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2024)
The increasing number of deaths and the rising risk of complications underscore the importance of managing and controlling hypertension. Knowledge and adherence to hypertension management are crucial factors in controlling blood pressure and its complications. Patient compliance in managing hypertension is vital to prevent potentially fatal complications. However, insufficient knowledge about prevention can impact adherence levels. This study aims to explore the relationship between hypertension knowledge and adherence to complication prevention among hypertensive patients in Cimanggung Village. This was quantitative observational analytic research with a cross-sectional approach involving 95 respondents in Cimanggung Village. The sampling technique used proportional random sampling method. The research instruments used are the hypertension knowledge level scale questionnaire and the hypertension complication prevention adherence questionnaire. The Spearman-Rank statistical test resulted in a p-value of 0.023 (p<0.05), indicating that there is a relationship between knowledge and compliance with hypertension complication prevention. Better knowledge about hypertension correlates with improved adherence to complication prevention measures. The majority of respondents have good knowledge and are mostly adherent to complication prevention measures. Increasing knowledge is expected to enhance patients' compliance in adhering to treatment and preventing complications. The suggestion of this research is to conduct a directed and sustainable education program to the people of Cimanggung Village about the importance of managing hypertension and preventing its complications